Limit cycles bifurcating from piecewise quadratic systems separated by a straight line. (July 2020) - Peng, Linping; Gao, Yunfei; Feng, Zhaosheng
Abstract: In this paper, we are concerned with limit cycles bifurcating from piecewise quadratic systems separated by a straight line. By means of the first-order averaging theory of discontinuous differential systems and the Argument Principle, we present an estimate of the maximum number of limit cycles bifurcating from the period annulus around the center of piecewise smooth systems.